Acidic and basic pre-treatments of agroindustrial residues for obtaining second generation ethanol - Sant’Anna, Ana Carolina Moreira; Tabai, Letícia; Maldonado, Rafael Resende (Revista Hipótese, 2020)
The present study investigated the application of acid (with H2SO4) or basic (NaOH) pretreatment for 2G ethanol production using two agro-industrial residues (orange pomace and soy molasses). The highest yields of conversion of residues into fermentable sugars were 37.7% (orange pomace/acid medium); 32.8% (orange pomace/basic medium) and 27.5% (soy molasses/acid medium). Ethanol production was higher in media that underwent acid pretreatment, reaching a maximum of 3.8% v/v for orange pomace.
Keywords: Orange pomace; Second generation ethanol; Soybean molasses; Pretreatment